Application of radio frequency identification technology in sports equipment management in universities - Zhifang, XIAO; Wentao, GUO (Edelweiss Applied Science and Technology, 2025)
This study aims to address prevalent challenges in university sports equipment management, such as inventory inaccuracy, high loss rates, operational inefficiency, and inadequate maintenance, by designing and implementing an automated management system based on UHF RFID technology. The system is built on a three-layer architecture (Perception, Network, Application) and utilizes customized durable RFID tags, fixed and handheld readers, and a comprehensive software platform integrating inventory management, transaction processing, and maintenance alerts. A three-month pilot study was conducted, tracking over 300 items to evaluate system performance. The results demonstrated a 99.8% inventory accuracy rate, a 60% reduction in audit time, a 60% decrease in equipment loss, and over 75% improvement in checkout/return efficiency. The system also enabled predictive maintenance alerts based on usage data. The RFID-based system proves to be a robust, scalable, and highly efficient solution, significantly enhancing management practices. This system modernizes asset tracking in educational institutions, leading to substantial cost savings, optimized staff allocation, extended equipment lifespan through proactive maintenance, and improved user satisfaction. The architecture also provides a scalable platform for managing other mobile university assets.